Asupan Telur Ayam Rebus Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil - Femmy Keintjem; Yusupin Muyono Essing; Sjenny Olga Tuju; Robin Dompas; Anita Lontaan (JIDAN (Jurnal Ilmiah Bidan), 2022)
Background: One of the biggest causes of maternal mortality is bleeding due to anemia. Pregnancy makes big changes to the body of a pregnant woman, one of the changes that occurs is the hematological system. Purpose : this study was to determine the effect of intake of boiled chicken eggs on increasing hemoglobin levels in pregnant women at the Melonguane Health Center, Talaud Islands District. Method : This type of research is quasi experiment using pre test-post test with one group design which was carried out on 19 samples determined by purposive sampling. Collecting data using a pre-test post-test checklist observation sheet and an observation checklist sheet for giving boiled chicken eggs. Data analysis used the Wilcoxon with a significance p value <0.05. Results: test Wilcoxon showed the effect of consuming boiled chicken eggs on a significant increase in hemoglobin levels of pregnant women with a ρ value of 0.001 <0.05. The average difference in hemoglobin levels before and after the intervention was 1.13. It is recommended that pregnant women consume boiled chicken eggs to help improve nutritional status in preventing anemia in pregnant women.